How Digital Intelligence Enables Integration of Agricultural and Tourism Industries? An Empirical Study of Less-Developed Areas in China - Xin Yang; Chongli Chen; Shijiao Huang; Congxian He (SAGE Open)
The integration of agricultural and tourism industries is an important way for underdeveloped regions to build economic development momentum with a distinctive industrial system, and digital technology or artificial intelligence provides opportunities for industrial integration and innovative development. Using panel data from 17 prefecture-level cities in the former Central Soviet Area of Jiangxi, Fujian, and Guangdong Provinces spanning from 2012 to 2021, this study empirically examines the impact of digital intelligence on the integration of agricultural and tourism industries, along with its underlying mechanisms. The empirical results show that digital intelligence can significantly promote the integration of agricultural and tourism industries, but intelligence contributes less to the integration of agricultural and tourism than digitization. In addition, digital intelligence promotes the integration of agricultural and tourism industries through the industrial structure, threshold-lowing, and consumer demand effects. Moreover, the empowering effect of digital intelligence in the cities of the Jiangxi Region is greater than that of the Fujian and Guangdong Regions.